The Impact of Slang Language Used By “Gen Z” On The Existence of Indonesian Language - Zulkhaeriyah Zulkhaeriyah; Dede Rosyadi ZA; Tri Pujiati (ELS Journal on Interdisciplinary Studies in Humanities, 2023)
Social media is enlivened by young people and does not rule out the possibility of the elderly enlivening it. Not only that, the creativity shown by young people in this era of modernization also gives rise to language variations that are varied from the standard or correct language in terms of grammar, but are made simpler, shorter, so that what is called among young people is slang.This research aims to find out the impact of Language Slang used by “Gen Z” towards the existence of Indonesian language; The research method used by researchers is descriptive qualitative research method. This research uses data collection techniques with documentation, listening and recording which is sourced from social media such as, Twitter, WA, and TikTok. The result shows that slang have an impact on enriching and expanding the vocabulary of the Indonesian language. On the other hand, the bad impact of the use of Slang are Indonesian is in danger of being replaced by slang, decreasing the degree of Indonesian, causing the extinction of the Indonesian language. Some terms or slang can become popular and widely used by the community so that they become part of the broader Indonesian language. So it is very importance to balance the use of slang with the ability to use good and correct Indonesian in a formal or professional context. This can also be done by improving understanding of grammar rules as well as learning to use more appropriate and standardized vocabulary in formal situations.